ANALYSIS OF THE INFLUENCE OF HBSAG DETECTION RESULTS ON THE INTERPRETATION OF ANTI-HBC RESULTS IN THE DIAGNOSIS OF HEPATITIS B INFECTION - Pramonodjati, Fredericus; Arini, Liss Dyah Dewi; Martins, Santana; Pasha, Erlanda Islami (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
This study aims to analyze the relationship between Hepatitis C Virus Antibody (anti-HCV) test results using the ELISA method and Hepatitis B surface Antigen (HBsAg) test results using the rapid test method. HBV and HCV co-infection is a clinically relevant issue as it can accelerate the progression of chronic liver disease. Data from 62 patient samples were analyzed using the Chi-Square test to examine the significance of the relationship between these two categorical variables. The statistical analysis revealed a Chi-Square value of 3.89 with a P-value of 0.048, which is below the 0.05 significance level. This finding indicates a statistically significant association between the HBsAg and anti-HCV test results. This study concludes that in the sampled population, a reactive result on one test is associated with reactivity on the other, highlighting the importance of dual screening for both viruses in high-risk populations.